High basal protein kinase A-dependent phosphorylation drives rhythmic internal Ca2+ store oscillations and spontaneous beating of cardiac pacemaker cells - Vinogradova, Tatiana M; Lyashkov, Alexey E; Zhu, Weizhong; Ruknudin, Abdul M; Sirenko, Syevda; Yang, Dongmei; Deo, Shekhar; Barlow, Matthew; Johnson, Shavsha; Caffrey, James L; Zhou, Ying-Ying; Xiao, Rui-Ping; et al. (Circulation research, 2006)
Local, rhythmic, subsarcolemmal Ca2+ releases (LCRs) from the sarcoplasmic reticulum (SR) during diastolic depolarization in sinoatrial nodal cells (SANC) occur even in the basal state and activate an inward Na(+)-Ca2+ exchanger current that affects spontaneous beating. Why SANC can generate spontaneous LCRs under basal conditions, whereas ventricular cells cannot, has not previously been explained. Here we show that a high basal cAMP level of isolated rabbit SANC and its attendant increase in protein kinase A (PKA)-dependent phosphorylation are obligatory for the occurrence of spontaneous, basal LCRs and for spontaneous beating. Gradations in basal PKA activity, indexed by gradations in phospholamban phosphorylation effected by a specific PKA inhibitory peptide were highly correlated with concomitant gradations in LCR spatiotemporal synchronization and phase, as well as beating rate. Higher levels of basal PKA inhibition abolish LCRs and spontaneous beating ceases. Stimulation of beta-adrenergic receptors extends the range of PKA-dependent control of LCRs and beating rate beyond that in the basal state. The link between SR Ca2+ cycling and beating rate is also present in vivo, as the regulation of beating rate by local beta-adrenergic receptor stimulation of the sinoatrial node in intact dogs is markedly blunted when SR Ca2+ cycling is disrupted by ryanodine. Thus, PKA-dependent phosphorylation of proteins that regulate cell Ca2+ balance and spontaneous SR Ca2+ cycling, ie, phospholamban and L-type Ca2+ channels (and likely others not measured in this study), controls the phase and size of LCRs and the resultant Na(+)-Ca2+ exchanger current and is crucial for both basal and reserve cardiac pacemaker function.